PENGARUH KUALITAS LAYANAN DAN PROMOSI TERHADAP PREFERENSI ANGGOTA DALAM PENGAJUAN PEMBIAYAAN MUDHARABAH DI KJKS BMT-MMU CABANG SIDOGIRI PASURUAN - Fatmah, Fatmah; Virdiany, Fitri (el-Qist : Journal of Islamic Economics and Business (JIEB), 2014)
KJKS BMT-MMU Sidogiri Pasuruan is one of financial institutions which done by akad with duniawi and ukhrawi basic, because akad is done according to Islamic law (Shariah). The goal of this research is to analyze the influence of service quality and promotion to member’s preference in proposing mudharabah defrayal at KJKS BMT-MMU Branch Sidogiri Pasuruan. Service quality, promotion, and member’s preference is one union which difficult to be dissociated, because the service quality and promotion which is given to a company has direct effect to member’s preference. This research is quantitative research with survey method, the goal of this research is to know the influence of service quality and promotion to member’s preference in proposing mudha’arabah defrayal at KJKS BMT-MMU Branch Sidogiri Pasuruan. To know this, it is used double linier analysis regress with F test and t test. The amount of sample n this research is 57 members with determinant sample used purposive sampling technique. The technique of data collection use questionnaire, interview, documentation, and observation, while to test the instrument used validities, reliabilities, and classic assumption test. Based on the result of the coefficient regress test stimultan (F test) is obtained F count is 2,398 with F table 3,17. Because F count is smaller than F tab;e, therefore it can be said that service quality and promotion have no influence significantly to member’s preference in proposing mudharabah defrayal. The result of coefficient regress partially (t test) is obtained service quality variable has t count 1,058 and promotion variable has t count 0,956. Both of variables have no influence significantly to member’s preference in proposing mudharabah defrayal. This matter is shown by t count is smaller that t table (2,000).